The effect of metformin treatment on the serum levels of homocysteine, folic acid, and vitamin B12 in patients with polycystic ovary syndrome - Sedigheh Esmaeilzadeh; Maryam Gholinezhad-Chari; Reza Ghadimi (Wolters Kluwer Medknow Publications, 2017)
Background and Objective: Hyperhomocysteinemia is a well-known risk factor for cardiovascular disease. Although metformin therapy can increase homocysteine (Hcy) levels, it frequently is used as an oral medicine in women with polycystic ovary syndrome (PCOS), who might be at risk of catching diabetes mellitus. The aim of this study was to investigate the effect of metformin on the levels of serum Hcy, vitamin B12 (vit B12), and folic acid in patients with PCOS. Materials and Methods: An interventional study was designed with 18 patients with PCOS at the Fatemehzahra infertility Hospital in Babol, Iran. Metformin treatment (500 mg twice daily) was initiated in all patients for a period of consecutive 6 months. The levels of serum Hcy, vit B12, and folic acid were measured in the participants before and after metformin treatment. Results: The mean vit B12 level showed a significant decrease in patients after 6 months of metformin treatment (P = 0.002). However, there was no significant difference in serum folic acid levels. The mean Hcy levels increased after treatment, but this difference not was statistically significant. When patients were stratified into four subgroups by their insulin sensitivity and body mass index (BMI), relatively similar results were obtained in the subgroups, except that Hcy levels in the overweight/obesity group (BMI > 25 kg/m2) after treatment showed a significant increase (P = 0.01). Conclusion: These findings indicate that metformin increases the serum Hcy concentration in patients with PCOS especially in the women with BMI > 25 kg/m2. The possible mechanism for this effect would be the obvious reduction in the levels of vit B12.